2020
DOI: 10.1038/s41467-020-16550-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the transcription factor MAFB limits β-cell derivation from human PSCs

Abstract: Next generation sequencing studies have highlighted discrepancies in β-cells which exist between mice and men. Numerous reports have identified MAF BZIP Transcription Factor B (MAFB) to be present in human β-cells postnatally, while its expression is restricted to embryonic and neo-natal β-cells in mice. Using CRISPR/Cas9-mediated gene editing, coupled with endocrine cell differentiation strategies, we dissect the contribution of MAFB to β-cell development and function specifically in humans. Here we report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 82 publications
4
44
0
Order By: Relevance
“…This is consistent with a recent report showing that in mice, MAFB does not compensate for MAFA loss 12 . Further, our data highlights MAFB as playing a key role in defining both β and α cell identity, in line with a recent report where MAFB deletion in human embryonic stem cells disrupted the differentiation process for both β and α cells 55 . Thus, our approach highlights how transcription factor profiles at the single cell level can be used to predict transcriptional and functional consequences of genetic manipulation, highlighting an immense power for large scRNA-seq datasets.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with a recent report showing that in mice, MAFB does not compensate for MAFA loss 12 . Further, our data highlights MAFB as playing a key role in defining both β and α cell identity, in line with a recent report where MAFB deletion in human embryonic stem cells disrupted the differentiation process for both β and α cells 55 . Thus, our approach highlights how transcription factor profiles at the single cell level can be used to predict transcriptional and functional consequences of genetic manipulation, highlighting an immense power for large scRNA-seq datasets.…”
Section: Discussionsupporting
confidence: 92%
“…Single-cell RNA sequencing (scRNA-seq) and other assays of global transcription have been used to rigorously study and uncover pancreatic identities ( Augsornworawat and Millman, 2020 ), including assessment of SC-β Cell populations in diabetic models ( Balboa et al, 2018 ; Maxwell et al, 2020 ), analysis of SC-islets from in vitro differentiation ( Pagliuca et al, 2014 ; Veres et al, 2019 ), and studying islets or islet development ( Baron et al, 2016 ; Byrnes et al, 2018 ; Enge et al, 2017 ; Hogrebe et al, 2020 ; Muraro et al, 2016 ; Russell et al, 2020 ; Scavuzzo et al, 2018 ; Segerstolpe et al, 2016 ; Velazco-Cruz et al, 2020a ; Xin et al, 2018 ). When compared to β Cells from cadaveric islets, these technologies revealed that in-vitro -derived SC-β Cells lack or have low expression of many important maturation genes, such as MAFA and G6PC2 ( Hogrebe et al, 2020 ; Pagliuca et al, 2014 ; Veres et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The human MAFA S64F :MAFB heterodimeric activator could impart a unique influence on β cells compared to the mouse MafA S64F :MafA homodimeric activator (Cyphert et al, 2019; Hang and Stein, 2011), which may explain why neuroendocrine tumors and overt hypoglycemia was not observed in aged MafA S64F/+ mice (data not shown). Notably, MAFB was recently shown to be essential for the formation of human embryonic derived β cells and insulin production (Russell et al, 2020), whereas there is no phenotype associated with the loss of MafB in mouse islet β cells except during pregnancy (Cyphert et al, 2019). Thus, we believe that it will be important to extend the analysis of MAFA S64F control to human islets both acutely in vitro and chronically after transplantation of human pseudoislets into immunocompromised mice to directly determine its effect in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…While the role of MAFA or MAFB has not been analyzed directly in intact human islets, both are required for GSIS in the human EndoC-βH1 β cell line (Scharfmann et al, 2014;Scoville et al, 2015). Moreover, we have recently shown that MAFB is essential to insulin production in human embryonic stem cell derived β cells (Russell et al, 2020), which is in stark contrast to its dispensable role in rodents (Banerjee et al, 2016;Cyphert et al, 2019).…”
mentioning
confidence: 99%